Controlled Growth of CH3NH3PbBr3 Perovskite Nanocrystals via a Water–Oil Interfacial Synthesis Method. (22nd October 2019) - Li, Fangfang; Cao, Liya; Shi, Shuangshuang; Gao, Heng; Song, Li; Geng, Chong; Bi, Wengang; Xu, Shu
Abstract: Fundamental insights into the reaction kinetics of organic–inorganic lead halide perovskite nanocrystals (LHP NCs) are still limited due to their ultrafast formation rate. Herein, we develop a water–oil interfacial synthesis of MAPbBr3 NCs (MA=CH3 NH3 + ), which prolongs the reaction time to tens of minutes. This method makes it possible to monitor in situ the formation process of MAPbBr3 NCs and observe successive spectral evolutions from 438 to 534 nm in a single reaction by extending reaction time. The implementation of this method depends on reducing the formation rate of PbBr6 4− octahedra and the diffusion rate of MA. The formation of PbBr6 4− is a rate‐determining step, and the biphasic system offers a favorable reaction condition to control the mass transfer of MA. The effects of temperature and concentration of precursor and ligand are investigated in detail. Abstract : Wachstum unter der Zeitlupe : Eine umfangreiche kinetische Studie des Wachstumsmechanismus von MAPbBr3 ‐Nanokristallen (NCs; MA=CH3 NH3 + ) wurde durch eine Wasser/Öl‐Grenzflächensynthesemethode ermöglicht. Die gesamte Reaktionszeit der MAPbBr3 ‐NCs wird hierbei auf viele Minuten verlängert, indem die Bildungsrate der PbBr6 4− ‐Oktaeder und die Diffusionsrate von MA verringert werden.